Morphometric changes of the calcareous nannofossil taxon Discoaster multiradiatus across the Paleocene-Eocene Thermal Maximum: biotic and abiotic factors - B. De Bernardi; E. Erba; F. Tremolada (2007)
Size measurements of the calcareous nannofossil taxon Discoaster multiradiatus were carried out across the Paleocene-Eocene Thermal Maximum (PETM) in Ocean Drilling Program Holes 690B (Maud Rise, Weddell Sea) and 1209B (Shatsky Rise, Pacific Ocean). Morphometric investigations show that D. multiradiatus specimens are generally larger at ODP Site 1209 rather than at ODP Site 690. A small increase in size of this species is recorded at ODP Site 1209, whereas significant variations characterize ODP Site 690. A marked shift in diameter size was observed in the lower portion of the PETM at ODP Site 690, which coincides with the onset and the peak of the Carbon Isotope Excursion (CIE). The occurrence of the largest specimens of D. multiradiatus at the onset and the peak of the CIE coincides with an inferred massive introduction of carbon dioxide, increasing temperature, and a likely drop in primary productivity. This contradicts the size-reduction hypothesis under excessive pCO2 levels. Instead, the size increase of D. multiradiatus could be the result of a significant influx of larger-sized specimens from lower latitudes during the warmest and the most nutrient-depleted interval of the PETM. In addition, the shift in size recorded in the lower part of the PETM could result from the occurrence of a new echophenotype that occupied short-lived ecological niches triggered by changes in water stratification, temperature, and primary productivity